Crustal structure of the Carpathian Orogen in Romania from receiver functions and ambient noise tomography: how craton collision, subduction and detachment affect the crust. Issue 1 (16th March 2019) - Petrescu, Laura; Stuart, Graham; Tataru, Dragos; Grecu, Bogdan
SUMMARY: The structure and processes of collisional orogens at the edges of cratons are complex and the extent to which the crust is affected by subduction of cratonic material, slab break-off and post-collisional magmatism is poorly constrained. The Carpathian arc is an Alpine orogenic system, involving the collision and subduction of the East European Craton and the closure of the Tethys ocean. Unusual Neogene backarc magmatism developed after subduction ended ∼9 Ma ago and upper-mantle M w >7 earthquakes are associated with a relic slab actively breaking-off in the Vrancea Zone. To investigate the crustal and uppermost mantle structure, we analyse teleseismic earthquakes recorded at 56 broad-band seismic stations in Romania and Moldova. Using phase-weighted H − κ stacking of receiver functions, we estimate the bulk crustal thickness and Vp / Vs ratio, a good discriminant of crustal composition. This technique was used on all stations and assumes a single-layer crust with a discontinuity at its base. Additionally, by jointly inverting receiver functions and ambient noise we obtain shear wavespeed ( Vs ) models to ∼60 km depth beneath 34 stations and provide another independent measure of the Moho depth and its apparent seismic sharpness. Crustal thickness estimates from the two methods are inconsistent in regions where the Moho is gradational or an intracrustal discontinuity is more dominant. We support this interpretation with a range of synthetic tests. Above the actively detaching Vrancea slab, multiple intracrustal discontinuities and a gradational Moho are identified on Vs profiles, and high Vp / Vs (>1.83) are consistent with magmatic underplating. On the backarc side of the slab, magmatism-pervaded crust has low Vp / Vs signature (<1.73), consistent with felsic composition or the presence of water without extensive partial melt. In the backarc Transylvanian Basin and Apuseni Mountains, the upper mantle has anomalously low Vs (<4 km s −1 to 60 km depth), the crust is dominantly felsic and thin (<35 km), with a Moho probably inherited from the obducted Neo-Tethys ophiolites. On the forearc side, sedimentary basins have low Vs (<2.5 km s −1 ) and high Vp / Vs signatures (>1.8), indicating a high fluid-pressure regime. Finally, Precambrian units in the foreland are seismically heterogenous, with Moho depths of 30–50 km, and extend ∼100 km beneath the South and Southeast Carpathians, implying that the Vrancea slab underlies Precambrian-aged crust.